In Vitro Evaluation the Anti-Melanogenic Effects of Various Extracts of Oat Seeds: Anti-Melanogenic Effects of Oat Seeds - Shiva Alaghebandi; Zeinab Yazdiniapour; Fatemeh Shafiee (Iranian Journal of Pharmaceutical Sciences, 2022)
This study was designed to examine the effects of aqueous and hydroalcoholic extracts of oats (Avena sativa), which are rich in beta-glucan with established anti-pigmentation effects on the melanin biosynthesis rate in melanocyte cell cline, B16F10, as well as its safety effects on skin normal cells. Maceration method was used to extract the seed powder of Avena sativa and then the polysaccharide content was determined. The safety of extracts was analyzed using MTT assay on L-929 cells. The anti-melanogenic effects of the extracts were determined using the calculation of mushroom tyrosinase inhibitory effects, the B16F10 treated cells assay for evaluating the extracts tyrosinase inhibitory effects and the melanin contents, in comparison to the PBS as the negative control. Our results showed that the aqueous and hydroalcoholic extracts had no significant toxicity on L-929 normal cells. In comparison to the Kojic acid used at the EC50 concentration (3 µg/ml), both aqueous and hydroalcoholic extracts led to mushroom and intracellular tyrosinase inhibition as well as reduction in melanin content of B16F10 treated cells, concentration dependently, especially at the highest concentration, 5 mg/ml. Finally, the total polysaccharide count in water and hydroalcoholic extracts was calculated as about 2.9 and 2.8 µg, respectively, for 5 µg of dried extracts. In conclusion, this study has proven the anti-melanogenic and tyrosinase inhibitory effects of Avena sativa extracts without any toxic effects on skin normal cells in the effective concentrations. So, with reliable laboratory effectiveness, attempts to prepare suitable formulation from this herb is therefore suggested.